Analysis Improvement of Helpdesk System Services Based on Framework COBIT 5 and ITIL 3rd Version (Case Study: DSIK Airlangga University) - Laqma Dica Fitrani; R. V. Hari Ginardi (IPTEK Journal of Proceedings Series, 2019)
Airlangga University has a helpdesk system that is tasked to help overcome the problems related to the use of information technology facilities that can be utilized by the academic community. This system is managed by the Directorate of Information System. Currenty, there are many complaints handled by the helpdesk that make it difficult to handle problems, the escalation of problem handling is still not optimal, complaint handling is not in accordance with the time set, and still miss communication between the helpdesk and the unit responsible for completing the complaint. Based on the problems, improvement analysis of the helpdesk system services is required. The service analysis of the helpdesk system will be done using the COBIT 5 and ITIL V3 framework. Data were obtained through interviews and questionnaires distributed to RACI Chart based on domains selected which is DSS01. The data is processed to obtain the level of capability (As Is) and the expected condition (To Be), then gap analysis of these two conditions to be used as the basis of the information technology governance improvement strategy in managing the helpdesk system. The improvement plan is done by combining COBIT with ITIL V3. From this research, the current capability values at level 1 and to be values at level 4, so the gap value obtained is 3. The result of the capability value analysis and gap is used to make the recommendation of continuous improvement to achieve the to be value and the governance plan on incident management based on ITIL V3 framework